Pengaruh Event Service Quality terhadap Kepuasan Pengunjung dalam Event HOMEDEC 2018 - Jessica Pingkan Nikita (Bisnis Event, 2020)
The purpose of this study is to show how the value of service quality, and convenience encourage customer satisfaction among visitors of HOMEDEC 2018. The design of this study used a survey to interview visitors for testing hypothesis. Meanwhile the data needed for this study are about service quality of the event and the convenience of the event as the dependent variable and satisfaction with the venue as an independent variable. The aggregate number of visitors who were respondents this study was 186 visitors. Analysis of the data used in this study using questionnaires. The result of this research concludes that perceived service from the visitor of Event HOMEDEC 2018 is The Event is good enough because the event achieved high level of satisfaction from the quality of services expected to achieve event satisfaction.